Pembelajaran Sejarah pada SMAN di Daerah Terdepan Terluar Tertinggal (3T) Kepulauan Tanimbar Provinsi Maluku - Boni Marian (Jurnal Pendidikan Sejarah, 2019)
Abstract: This study aims to describe teacher preparation before conducting history learning at State Senior High School in the Frontier, Outermost, and Disadvantaged Region (3T) of Tanimbar Islands, and the history learning process at State Senior High School in the Frontier, Outermost, and Disadvantaged Region of Tanimbar Islands. This study uses descriptive qualitative methods, using data collection techniques through observation, interviews and documentation. Informants in this study are Principals, Teachers and Students at State Senior High School of Tanimbar Islands. The results of this study indicate that starting from preparation to the process of history learning in the State Senior High School in Tanimbar Islands has not run optimally. Facility problems negligence of school leaders, unprofessional teachers at work and lazy students are the main factors in the process of history learning in the Frontier, Outermost, and Disadvantaged Region (3T). Key word: Region 3T, Learning Process, History Learning